Judicial Oversight of the Discretionary Power of the Secretary-General in Imposing Disciplinary Measures - Aziz, Qahtan Adnan; Mohammed, Amjad Hakim (Journal of Ecohumanism, 2025)
Under the basic regulations, international public service regulations, and other administrative publications, the Secretary-General typically enjoys broad discretionary powers in areas such as appointments, promotions, terminations, and the imposition of disciplinary measures, as well as other authorities specified in these texts. Consequently, each legal system contains specific rules and standards of conduct that international employees must not violate. In the event that an employee fails to comply with their obligations or refrains from fulfilling them, they are considered in violation of their international duties, which requires the Secretary-General, based on their discretionary powers, to impose disciplinary measures. However, administrative stubbornness may sometimes lead to the issuance of a decision that, although it is fundamentally within the discretionary power of the administration, may adversely affect the employee’s position in a way that contradicts justice. Therefore, international administrative courts have played a significant role in exercising oversight over the administration’s discretionary power by restricting the issuing authority to the legal texts that granted it this right, using various methods that have been established through judicial precedents.